College of education students’ perceptions of their computational thinking proficiency - Gasaymeh, AlMothana; AlMohtadi, Reham (Frontiers in Education, 2024)
This study aimed to investigate college of education students' level of computational thinking proficiency and the differences in their level based on their demographic characteristics i.e., gender, program, and age. The study used a descriptive research design in which 190 students in the College of Education completed a computational thinking questionnaire. The computational thinking scale consisted of five dimensions i.e., creativity, algorithmic thinking, cooperativity, critical thinking, and problem-solving. The results showed that the level of computational thinking among students was diverse and fell within a moderate range. Genderbased analysis indicated a significant difference in only one dimension of computational thinking i.e., algorithmic thinking, with females scoring lower than males. In addition, based on students' academic program, significant variations were observed in algorithmic thinking and overall computational thinking levels, particularly between Bachelor and PhD programs, with PhD students scoring higher than Bachelor students. Additionally, the age-based analysis highlights significant differences, with older students consistently outperforming younger ones across various computational thinking dimensions. Based on the findings a set of recommendations was provided.